A descriptive grammar of early Old Japanese prose - Bentley, John R. (Brill, 2001)
The oldest written stage of the Japanese language forms the subject of John Bentley's important volume. The underlying texts (also presented here) are those of the religious liturgies (norito) and imperial edicts (A.D. 685).
Keywords: Japanese language -- To 794 -- Grammar.; Japanese language -- Grammar, Classical.; Japonais (Langue) -- Jusqu'à 794 -- Grammaire.; FOREIGN LANGUAGE STUDY -- Japanese.; Japanese language -- Grammar; Japanese language -- Grammar, Classical; Religiöse Literatur; Deskriptive Grammatik; Japans.; Língua japonesa.; Gramática.; Altjapanisch.; To 794; Electronic book.